EIF2AK2 Missense Variants Associated with Early Onset Generalized Dystonia. Issue 3 (15th December 2020) - Kuipers, Demy J. S.; Mandemakers, Wim; Lu, Chin‐Song; Olgiati, Simone; Breedveld, Guido J.; Fevga, Christina; Tadic, Vera; Carecchio, Miryam; Osterman, Bradley; Sagi‐Dain, Lena; Wu‐Chou, Yah‐Huei; Chen, Chiung C.; et al.
Abstract : Objective: The study was undertaken to identify a monogenic cause of early onset, generalized dystonia. Methods: Methods consisted of genome‐wide linkage analysis, exome and Sanger sequencing, clinical neurological examination, brain magnetic resonance imaging, and protein expression studies in skin fibroblasts from patients. Results: We identified a heterozygous variant, c.388G>A, p.Gly130Arg, in the eukaryotic translation initiation factor 2 alpha kinase 2 ( EIF2AK2 ) gene, segregating with early onset isolated generalized dystonia in 5 patients of a Taiwanese family. EIF2AK2 sequencing in 191 unrelated patients with unexplained dystonia yielded 2 unrelated Caucasian patients with an identical heterozygous c.388G>A, p.Gly130Arg variant, occurring de novo in one case, another patient carrying a different heterozygous variant, c.413G>C, p.Gly138Ala, and one last patient, born from consanguineous parents, carrying a third, homozygous variant c.95A>C, p.Asn32Thr. These 3 missense variants are absent from gnomAD, and are located in functional domains of the encoded protein. In 3 patients, additional neurological manifestations were present, including intellectual disability and spasticity. EIF2AK2 encodes a kinase (protein kinase R [PKR]) that phosphorylates eukaryotic translation initiation factor 2 alpha (eIF2α), which orchestrates the cellular stress response. Our expression studies showed abnormally enhanced activation of the cellular stress response, monitored by PKR‐mediated phosphorylation of eIF2α, in fibroblasts from patients with EIF2AK2 variants. Intriguingly, PKR can also be regulated by PRKRA (protein interferon‐inducible double‐stranded RNA‐dependent protein kinase activator A), the product of another gene causing monogenic dystonia. Interpretation: We identified EIF2AK2 variants implicated in early onset generalized dystonia, which can be dominantly or recessively inherited, or occur de novo. Our findings provide direct evidence for a key role of a dysfunctional eIF2α pathway in the pathogenesis of dystonia. ANN NEUROL 2021;89:485–497